2018
DOI: 10.1186/s12951-018-0364-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of cilomilast-loaded phosphatiosomes to suppress neutrophilic inflammation for attenuating acute lung injury: the effect of nanovesicular surface charge

Abstract: BackgroundCilomilast is a phosphodiesterase 4 (PDE4) inhibitor for treating inflammatory lung diseases. This agent has a narrow therapeutic index with significant adverse effects on the nervous system. This study was conducted to entrap cilomilast into PEGylated phosphatidylcholine-rich niosomes (phosphatiosomes) to improve pulmonary delivery via the strong affinity to pulmonary surfactant film. Neutrophils were used as a cell model to test the anti-inflammatory activity of phosphatiosomes. In an in vivo appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…In addition, we also detected apoptotic cells in lung by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining (Ding et al, 2019). Other studies reported IL-6, TNF-a, and H&E staining could assess the severity of ALI (Sun et al, 2011;Liu et al, 2018;Su et al, 2019b). Here, we demonstrated indicators that support ADMSCs-driven reduction of ALI induced by sepsis.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, we also detected apoptotic cells in lung by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining (Ding et al, 2019). Other studies reported IL-6, TNF-a, and H&E staining could assess the severity of ALI (Sun et al, 2011;Liu et al, 2018;Su et al, 2019b). Here, we demonstrated indicators that support ADMSCs-driven reduction of ALI induced by sepsis.…”
Section: Discussionsupporting
confidence: 59%
“…This is used to synthesize other different colloidal nanoparticles made up of organic or hybrid materials. These colloidal nanoparticles have a negative Z-potential, as has been previously reported [ 41 , 42 , 43 , 44 , 45 , 46 ], and the value of the negative charge depends on the medium in which the colloidal nanoparticles are diluted/dispersed, before the analysis, as well as other components of the pharmaceutical formulations [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 63%
“…For example, agents that show remarkable selectivity for subfamilies of PDE4 are showing promising results in mouse models of learning and memory and translation to human disease would be a game changing advance (135). Additionally, novel delivery systems are being developed that can transport PDE inhibitors to precise tissues or cell types, thereby abrogating complications associated with systemic distribution (e.g., (293,294)). In the future, novel delivery systems such as these could be employed to deliver agents that specifically disrupt the anchoring of single isoforms.…”
Section: Discussionmentioning
confidence: 99%